The Influence of the Three Step Interview Learning Model on Learning Outcomes in Pancasila and Citizenship Education - Rahmadani, Widya; Gimin, Gimin; Haryono, Haryono (CV. Rayyan Dwi Bharata, 2023)
This research aims to determine the effect of the three step interview learning model on the Civics learning outcomes of SMAN 3 Pekanbaru students. This research uses an experimental method with a Pretest-Posttest Control Group design. The population in this study was 341 people with the number of samples taken using a purposive sampling technique, namely 70 people consisting of MIPA 2 and MIPA 3 students at SMAN 3 Pekanbaru. The data collection technique uses pre-test and post-test results in the form of multiple choice questions. The results of this research show differences in learning outcomes from the two classes with the average scores obtained in the experimental class and control class, namely 82.63 and 75.51. Based on the results of calculating the hypothesis test with SPSS using the t test, it is obtained that tcount ttable with df=68 and a sign level of 5%=0.05, namely 4,846 1.995, it can be said that Ho is rejected and Ha is accepted, in other words there is a significant influence from the use of the learning model. three step interview on PPKn learning outcomes of SMAN 3 Pekanbaru students.